1986
DOI: 10.1172/jci112295
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induces DNA damage in cultured human endothelial cells.

Abstract: Morphologic and functional abnormalities of vascular endothelium are well recognized in diabetes. In view of our previous finding that high glucose concentrations accelerate death and hamper replication of cultured human endothelial cells, we have investigated in the same model the possibility that exposure to high glucose may result in DNA damage. DNA from human endothelial cells-but not from fibroblasts-exposed to 30 mM glucose for 9-14 d manifested an accelerated rate of unwinding in alkali indicative of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(132 citation statements)
references
References 27 publications
7
114
0
3
Order By: Relevance
“…Dandona et al (24) have demonstrated in a clinical study with diabetic subjects and healthy volunteers that diabetes is associated with increased production of reactive oxygen species and greater oxidative damage to DNA. In an experimental study, high glucose itself was shown to induce DNA damage (25). Thus, it is possible that increased production of reactive oxygen species or high glucose itself contributes to DNA damage, which may lead to mutational changes in oncogenes and tumor suppressor genes, and thereby to the development of gastric cancer.…”
Section: Results -mentioning
confidence: 99%
“…Dandona et al (24) have demonstrated in a clinical study with diabetic subjects and healthy volunteers that diabetes is associated with increased production of reactive oxygen species and greater oxidative damage to DNA. In an experimental study, high glucose itself was shown to induce DNA damage (25). Thus, it is possible that increased production of reactive oxygen species or high glucose itself contributes to DNA damage, which may lead to mutational changes in oncogenes and tumor suppressor genes, and thereby to the development of gastric cancer.…”
Section: Results -mentioning
confidence: 99%
“…In mesangial cells exposed to HG, the mixture of vascular factors changed to an antiangiogenic combination that has a negative effect on the growth and matrix of endothelial cells including disrupting their differentiation and ability to form capillary structures. In the diabetic patient glucose itself is toxic to endothelial cells, [45][46][47] but the antiangiogenic vascular growth factors secreted by mesangial cells may cause an additional disruptive effect causing endothelial injury and leading to glomerulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…18 High glucose induces DNA damage in cultured human endothelial cells. 19 Cellular adhesion molecules mediating homotypic and heterotypic cellular interactions have also been implicated in the various stages of tumor progression and metastasis. 20 Patients with noninsulindependent diabetes mellitus are characterized by insulin resistance, compensatory hyperinsulinemia, and increased growth factor production.…”
Section: Discussionmentioning
confidence: 99%